Curvilinear Relations between Age and Hemostatic Parameters in Chinese - Yeh, Chih-Jung; Pan, Wen-Harn; Bai, Chyi-Huey; You, May-Su; Wang, Weih-Cinn; Wang, Liang-Yueh; Lee, Ti-Kuang (Thrombosis and Haemostasis, 1994)
The role of hemostatic factors in the pathogenesis of cardiovascular disease has gained much attention recently. Information about hemostatic factors, and their age patterns is sparse for orientals. With the data collected in the Cardiovascular Disease Risk Factor Two-township Study in Taiwan, this study shows that, in general, the older the age, the stronger the tendency toward thrombosis. With advancing age, prothrombin time, activated partial thromboplastin time, and antithrom-bin-III level decreased steadily; but mean values of fibrinogen, factor VIIc, and factor VIIIc increased. Gender differences in the age patterns of the above factors are carefully described. Curvilinear relations between hemostatic factors and'age were demonstrated for adults aged 18 and above for all hemostatic factors studied. This curvilinearity should be taken into consideration when adjusting for the effect of age in data analysis to avoid residual confounding, particularly when the age range of the study subjects is wide.